Implementasi Metode Talaqqi dalam Meningkatkan Kemampuan Membaca Kitab Kuning - Eri Marta janil; Hamzah Irfanda; Nora Afnita; Aulia Auliafitri (Laskar Karya, 2026)
Islamic boarding schools play an important role in shaping the character and religious understanding of students, but many students still experience difficulties in reading and understanding classical tafsir books, especially Tafsir Jalalain, which requires mastery of nahwu, sharaf, and the skill of reading Arabic texts without harakat. Previous studies generally discuss the talaqqi method in learning the Qur'an or yellow books in general, while studies that specifically examine its application in learning classical tafsir are still limited. Therefore, this study aims to analyze the implementation of the talaqqi method in improving the reading ability of Tafsir Jalalain at the Nurul Yaqin Gadur Islamic Boarding School. This study uses a qualitative approach with a field research type. Data were collected through observation, interviews, and documentation, then analyzed descriptively. The results showed that the talaqqi method, planned in a structured manner and implemented through direct interaction between teachers and students, significantly improved the accuracy of reading and understanding of verse meanings. The success of this method was supported by the role of teachers and student motivation, although challenges still existed in terms of facilities and the variety of learning resources. This research provides a theoretical contribution to the development of tafsir learning methodology and a practical contribution to improving the quality of classical tafsir learning in Islamic boarding schools.